Event-Triggered L 2 − L ∞ Exponential Consensus of Leader-Follower Multi-Agent Systems - Rong, Li (IEEE access, 2024)
This paper investigates the [Formula Omitted] exponential consensus control problem of leader-follower multi-agent systems based on an event-triggered strategy. It begins by establishing an error system and provides a sufficient condition guaranteeing exponential stability of the error system while satisfying the [Formula Omitted] performance index. Subsequently, utilizing the condition, a design method for the [Formula Omitted] controller is presented. Finally, through a numerical example, this paper discusses the relationship between optimal [Formula Omitted] performance index and the maximum sampling period under different topological structures. The effectiveness of the proposed theoretical framework is validated through the numerical example.